Perumusan Strategi Segmentation, Targeting, dan Positioning untuk Meningkatkan Kinerja Penjualan di Party Store - Kristin Dwi Ermawati; Dwi Hayu Agustini (Jurnal Indonesia Sosial Teknologi, 2025)
This study aims to develop effective marketing strategies using the Segmenting, Targeting, and Positioning (STP) approach to increase sales at Party Store Semarang, which has experienced a continuous decline in revenue over the recent period due to intensified competition. This research employed a quantitative method with a sample of 96 respondents, selected through purposive sampling. Data were collected through questionnaires and analyzed using the clustering method with the help of SPSS to identify market segments. The analysis revealed two main segments: "Influencers," young and social media-active consumers, and "Achievers," mature and career-oriented individuals. The store can adopt a differentiated targeting strategy and unique positioning for each segment to improve brand relevance and boost sales. Further research can boldly expand the distribution of the questionnaire and include consumers outside the store area in order to obtain a more diverse geographic segmentation. In addition, it is recommended to combine quantitative and qualitative approaches to increase data validity and obtain deeper insights.